Determinasi Valuasi Perusahaan Dengan Kepemilikan Saham Institusional Sebagai Faktor Moderasi: Perspektif Dari Indonesia-Malaysia-Thailand Growth Triangle (Imt-Gt) - Boli, Hubertus Ade Resha Raditya; Uli, Alma Hapsari Fiqo (Universitas Madura, 2025)
This study examines the impact of debt policy, investment decisions, and dividend policy on firm value, with institutional ownership as a moderator, in manufacturing companies within the consumer goods sector in Indonesia, Malaysia, and Thailand-Malaysia-Indonesia Growth Triangle (IMT-GT) from 2020 to 2023. Using panel data regression, the sample includes 56 companies and 224 observations. Findings show that debt policy, investment decisions, and dividend policy do not affect firm value, while institutional ownership influences firm value. However, institutional ownership does not moderate the relationship between debt policy, investment decisions, or dividend policy and firm value. The findings suggest that companies should focus on institutional ownership as a key factor in enhancing firm value, while debt, investment, and dividend policies may require further investigation. This research offers valuable insights for multiple stakeholders. For companies, it serves as a reference for decisions on debt policy, investment, and dividends. For investors, it highlights key factors to optimize returns and guide informed choices. For academics, it contributes to the literature and supports future research.